Pancreatic islet regeneration and some liver biochemical parameters of leaf extracts of Vitex doniana in normal and streptozotocin–induced diabetic albino rats - Okpe Oche; Ibrahim Sani; Njoku Godwin Chiaka; Ndidi Uche Samuel; Atabo Samuel (Asian Pacific Journal of Tropical Biomedicine, 2014)
Objective: To test two water soluble extracts (aqueous and ethanolic) obtained from the leaves of Vitex doniana in normal and streptozotocin-induced diabetic rats for their effects on pancreatic endocrine tissues and serum marker enzymes for a period of 21 d. Methods: A total of 55 rats divided into 11 groups of 5 rats each were assigned into diabetic and non-diabetic groups and followed by a daily administration of ethanolic and aqueous extracts for 21 d. Group 1 was the normal control while group 7 was treated with standard drug. Results: The histopathological studies of the diabetic rats indicated increase in the volume density of islets, percent of β-cells and size of islet in the groups that received the plant extracts, which suggested regeneration of β-cells along with β-cells repairs, as compared with the non-treated diabetic control which showed complete degeneration of the islet cells. There was significant reduction (P<0.05) in the serum activities of marker enzymes, alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase in diabetes treated rats, whereas an insignificant increase (P>0.01) in the serum activities of marker enzymes was observed for non-diabetic treated rats. Results of total bilirubin, direct bilirubin and unconjugated bilirubin showed that diabetic control group was significantly higher (P<0.05) in total bilirubin and unconjugated bilirubin compared with treated groups while non-diabetic treated groups showed no significant increase (P>0.01) in total bilirubin and direct bilirubin compared with the normal control. Conclusions: This herbal therapy appears to bring about repair/regeneration of the endocrine pancreas and hepatic cells protection in the diabetic rat.